Internal Control Systems and Performance of Microfinance Institutions in Uganda: A Case Study of Kabale Municipality - Nandaula, Mwebe Lilian (Kabale University, 2022)
A Research Dissertation Submitted in Partial Fulfilment of the Requirements for the Award of A Master’s Degree in Business Administration of Kabale University